2019
DOI: 10.1038/s41537-019-0076-x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired illness awareness in schizophrenia and posterior corpus callosal white matter tract integrity

Abstract: Impaired illness awareness (Imp-IA) in schizophrenia is associated with interhemispheric imbalance, resulting in left hemisphere dominance, primarily within the posterior parietal area (PPA). This may represent an interhemispheric “disconnection syndrome” between PPAs. To test this hypothesis, we aimed to determine if diffusion-based measures of white matter integrity were disrupted in the corpus callosal tracts linking PPAs (i.e., splenium) in patients with Imp-IA in schizophrenia. T1-weighted and diffusion-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…The splenium is a bulbous structure overlapping with the tela choroidea of the third ventricle and the mid-brain ( Knyazeva, 2013 ). Splenial FA was found to be lowest in schizophrenia patients with impaired illness awareness, as compared to patients with intact illness awareness and healthy controls ( Gerretsen et al, 2019 ). A handful of studies examined DTI indices in at-risk individuals, revealing distinct effects in the corpus callosum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The splenium is a bulbous structure overlapping with the tela choroidea of the third ventricle and the mid-brain ( Knyazeva, 2013 ). Splenial FA was found to be lowest in schizophrenia patients with impaired illness awareness, as compared to patients with intact illness awareness and healthy controls ( Gerretsen et al, 2019 ). A handful of studies examined DTI indices in at-risk individuals, revealing distinct effects in the corpus callosum.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the existing evidence for the involvement of WM deficits in schizophrenia seems robust ( Kubicki et al, 2007 , Tamnes and Agartz, 2016 , Vitolo et al, 2017 ), with the largest-to-date ENIGMA consortium meta-analysis (2359 controls, 1963 patients) reporting widespread microstructural abnormalities across all major WM fasciculi ( Kelly et al, 2018 ). Beyond to between-group differences from healthy controls (HC), numerous studies have identified significant associations between WM markers and (predominantly positive) symptoms ( Bopp et al, 2017 , Cheung et al, 2011 , Stämpfli et al, 2019 ), core cognitive functions ( Kochunov et al, 2017 ), but also theory of mind abilities ( Kim et al, 2021 ) and poor insight into illness ( Antonius et al, 2011 , Gerretsen et al, 2019 ). These associations were especially evident for frontal, fronto-temporal, and fronto-limbic tracts, the superior longitudinal fasciculus, and inter-hemispheric connections ( Kuswanto et al, 2012 , Parnanzone et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although evidence obtained from clinical cases of alien hand syndrome has indicated that the posterior corpus callosum that interconnects the parietal areas plays a role in maintaining an integrated sense of self with regard to self-body representation and awareness ( Uddin, 2011 , van der Knaap and van der Ham, 2011 ), limited attention has been directed at investigating the psychological aspects of the self in individuals with lesions affecting the corpus callosum. Notably, a few studies that used DTI have reported an association between the posterior corpus callosum and poor insights for psychiatric symptoms in patients with schizophrenia ( Gerretsen et al, 2019 , Kubota et al, 2012 ). In the present study, we extended previous evidence on the role of the posterior corpus callous in self-awareness for body and psychiatric symptoms to cognitive domains.…”
Section: Discussionmentioning
confidence: 99%
“…The strength of structural connectivity between regions with cortical thinning increased with illness severity and was the highest in treatment-resistant schizophrenia 67 . Plausibly, cortical thinning in brain regions implicated in insight impairment is more apparent in treatment-resistant schizophrenia due to prolonged aberrant connectivity between these interconnected brain regions 59 , 68 . Second, we used a single measure of insight into psychosis rather than statistically derived factors.…”
Section: Discussionmentioning
confidence: 99%